2014
DOI: 10.1111/jace.13014
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Wear of Soda Lime Silica Glass in Humid Environments

Abstract: The mechanochemical wear of multicomponent glasses was studied under controlled humidity conditions using a reciprocating ball-on-flat tribometer. For dry conditions, the surfaces were extensively damaged by scratching for all of the glasses, while for humid conditions the wear behavior varied with the glass composition suggesting a chemical effect on scratch behaviors of glass surfaces. The wear of soda lime silica (also called sodium calcium silicate) glass was suppressed with increasing humidity, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(112 citation statements)
references
References 23 publications
7
105
0
Order By: Relevance
“…Thus, it was believed the wear of glass in humid environments occurs through a mechanochemical process rather than a purely mechanical one. Besides, the wear resistance of soda-lime glass increased as environmental humidity increased, which was not observed for other glasses such as fused silica, borosilicate, and aluminosilicate glasses [18,19]. These results indicated that the water reactivity inside the wear track of the soda-lime glass substrate being rubbed with silica or borosilicate glass balls is quite different from other glasses.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Thus, it was believed the wear of glass in humid environments occurs through a mechanochemical process rather than a purely mechanical one. Besides, the wear resistance of soda-lime glass increased as environmental humidity increased, which was not observed for other glasses such as fused silica, borosilicate, and aluminosilicate glasses [18,19]. These results indicated that the water reactivity inside the wear track of the soda-lime glass substrate being rubbed with silica or borosilicate glass balls is quite different from other glasses.…”
Section: Introductionmentioning
confidence: 67%
“…A contact load of 0.2 N was used for all data shown in this paper. In our previous study, it was found that the glass surface is damaged at this load condition as long as detrimental tribochemical reactions are prevented by the adsorption of one monolayer of alcohol [18]. For a silicon nitride ball compressing a soda-lime-silica glass surface, the corresponding maximum Hertzian contact pressure was estimated to be 400 MPa.…”
Section: Experimental Methodsmentioning
confidence: 94%
See 3 more Smart Citations